2023
DOI: 10.1108/meq-03-2023-0091
|View full text |Cite
|
Sign up to set email alerts
|

What drives environmental, social and governance (ESG) performance? The role of institutional quality

Alan Bandeira Pinheiro,
Joina Ijuniclair Arruda Silva dos Santos,
Ana Paula Mussi Szabo Cherobim
et al.

Abstract: PurposeThis study aimed to investigate the role of the country's institutional quality on the environmental, social and governance (ESG) performance of its companies.Design/methodology/approachOver a four-year period (2016–2019), the study examined the ESG performance of 412 organizations situated in 19 countries. ESG performance was the dependent variable, and the independent variables were rule of law, economic freedom, education index and international trade freedom. These factors described the institutiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 70 publications
0
9
0
1
Order By: Relevance
“…Additionally, the impact of board factors, including gender diversity, has been studied in relation to ESG disclosure scores, with larger board sizes increasing ESG disclosure by bringing diverse perspectives (Bhatia & Marwaha, 2022). The institutional environment also plays an important role in influencing ESG performance, and institutional quality has a major impact on ESG performance outcomes (Pinheiro, 2023).…”
Section: Internal Factors Affecting Esg Integrationmentioning
confidence: 99%
“…Additionally, the impact of board factors, including gender diversity, has been studied in relation to ESG disclosure scores, with larger board sizes increasing ESG disclosure by bringing diverse perspectives (Bhatia & Marwaha, 2022). The institutional environment also plays an important role in influencing ESG performance, and institutional quality has a major impact on ESG performance outcomes (Pinheiro, 2023).…”
Section: Internal Factors Affecting Esg Integrationmentioning
confidence: 99%
“…In this sense, the social and environmental practices of a company are determined by the national business system of the country in which it is headquartered (Ioannou & Serafeim, 2012;Matten & Moon, 2008). More recently, Pinheiro et al (2023) found that the institutional environment can shape companies' behavior in relation to ESG performance. Therefore, companies adopt different environmental policies according to the institutional environment in which they operate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is important to investigate CSR reporting as it pertains to a wide set of stakeholders, who are concerned with long-term and ethical issues (Christensen et al, 2021). According to Pinheiro et al (2023), it is still unclear how national institutions shape companies' environmental behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Merlugo et al (2021) also showed the power of digital transformation in the Accounting professional's work. Other emerging issues in Accounting involve preparing official reports following the guidelines of the Sustainable Development Goals, as well as corporate involvement with ESG (Environmental, Social, and Governance) performance (Pinheiro et al, 2023).…”
Section: Appreciation Of the Accounting Professional In Brazilmentioning
confidence: 99%